Pengaruh Literasi Keuangan Terhadap Kesejahteraan PNS di Kota Bengkulu - Agfi Nur Mahdiyah; Sri Adji Prabawa (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
These findings are intended to examine the influence of financial literacy on the welfare of civil servants in Bengkulu City. Using the SEM model and SmartPLS 4.0 software, these findings analyze data from 60 respondents who are civil servants in Bengkulu City. The variables used in these findings are financial behavior, financial attitude and financial knowledge and welfare. The findings provide an indication that financial behavior, financial attitude and financial knowledge have a significant influence on the welfare of civil servants. Good financial behavior, positive financial attitude and adequate financial knowledge have been proven to improve the welfare of civil servants. This research provides new insight into the many factors that influence the welfare of civil servants and suggests that government agencies can consider these aspects in designing human resource development programs. In doing so, this research contributes to the behavioral finance and welfare literature of civil servants, as well as providing practical implications for human resource management in the public sector.